Isolamento de diterpenos e avaliação in vitro da atividade antimicrobiana frente a bactérias causadoras de mastite bovina - Fonseca, Ariana Aparecida Polo (2012)
Bovine mastitis is a high prevalence infectious disease that causes many injuries to the dairy cattle around the world and also in Brazil. It is caused by bacteria located in the mammary gland, causing lesions in the secreting tissues. Staphylococcus aureus, Streptococcus agalactiae, Streptococcus dysgalactiae, Escherichia coli and Staphylococcus epidermidis are the main species related to this pathology. Diterpenes are a wide and diversified class of natural products wich responsible for a number of important biological activities, including antibacterial. The present work describes the isolation and identification of major diterpenes such as manool, ent-caurenoic acid and ent-copalic acid, respectively isolated from Salvia officinalis, Mikania glomerata and Copaifera langsdorffii and also describes the evaluation of its antimicrobial potential against the main pathogens associated to bovine mastitis. In this investigation, it were determined the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (CBM) through the microdilution broth method and the time-kill curve of the most active compound against Staphylococcus aureus was plotted. In this sense, ent-copalic acid showed to be able to inhibit most of the investigated microorganisms in minimum inhibitory concentration and minimum bactericidal concentration values that can be considered very promising and also able to completely inhibit the S. aureus inoculums within 24 hours.